Biochemical Markers in the Early Diagnosis of Chronic Kidney Disease - Kifaya hassan Khadher; Zainab Majeed Odeh; Qasim Obayes Jasim; Fatima Ahmed Abdel Reda (American Journal of Biomedicine and Pharmacy, 2024)
Chronic kidney disease (CKD) is defined as kidney damage or decreased kidney filtration rate for a period ≥3 months and affects no less than 12.2% of the adult population worldwide. With a progressive increase in its prevalence, it is estimated that CKD, due to urbanization, population aging, and other risk factors, will become one of the top 10 most significant global health problems worldwide. This will increase the financial burden on healthcare, ranging between $650 and $923 billion. Among the 10 leading causes of death worldwide, chronic kidney disease has caused an estimated 6.8 million deaths in 2013, resulting in a mortality rate of 15%. However, in the same period, a relative reduction of 2.9% was observed for these deaths, due to worldwide interventions, raising disease awareness and attention. CKD is a symptom of a myriad of complex afflictions and is not easily diagnosed or staged by a sole test. Moreover, although incidence is until the age of 60 either steady or declining, the global prevalence of CKD is greater in adults up to 74 years old. CKD risk factors encompass age, diabetes, cardiovascular disease, and hypertension. Since the younger population has been increasingly affected by, for example, diabetes mellitus or hypertension, greater concerns are raised in terms of life expectancy and healthcare financial burden. It is crucial, and of urgent need, to identify and diagnose patients with CKD at its early stages in order to manage both the disease and its comorbidities. To achieve this, apart from decreasing the expense to handle unexpected non-communicable diseases, it is also important to find new non-traditional biochemical markers. So far, besides the omnipresent Urea and Creatinine, biomarkers such as β2-microglobulin, Cystatin C, Neutrophil Gelatinase-Associated Lipocalin, and Kidney Injury Molecule-1 have been proposed. Nevertheless, it is necessary to unveil potential biomarkers that can be used in panel as an enhanced tool for the early diagnosis of chronic kidney disease.